Volunteering in Health Care Context: A Concept Analysis Using Rodgerâ€™s Evolutionary Approach - A'la, Muhamad Zulfatul; Nuntaboot, Khanitta; Rungreangkulkij, Somporn (Department of Nursing, Faculty of Medicine, Diponegoro University, 2020)
Background: Volunteering is a common concept used in various disciplines including in the health care context. Nursing plays a role in volunteering concept development. However, the use of volunteering concept is still interchangeable. The clear definition concept about volunteering will promote the improvement in healthcare system quality.Purpose: This study aimed to clarify the volunteering concept in the health care context using Rodgerâ€™s evolutionary concept analysis.Methods: This study used a literature review for collecting the exemplars. Researchers used articles published in 2010-2020 in ScienceDirect, PubMed, Web of Science, and Google Scholar. Articles were searched using OR and AND. The keywords and MeSH used were â€œVolunteering OR Volunteerism OR volunteers AND Health OR Care OR Nursingâ€ in the title, abstract, and keyword articles. Inclusion criteria were full articles in English. Rodgerâ€™s evolutionary concept analysis was implemented in this study with six steps.Results: This study used 39 eligible articles analyzed by providing codes of each article and then classified them in attributes, antecedents, and consequences of concept. Five attributes of volunteering, namely, giving help freely, as long-term planned, as giving a benefit to another individual, group, or organization, as working at a formal organization, and as a long-life activity were found. Antecedents of volunteering include motivation, social demographic, and philanthropic behavior. The consequences of volunteering were consequences for volunteers, patients, and the health care system.Conclusion: Volunteering is a complex concept and many surrogate concepts have similar definitions. The attributes are still debatable and need to be explored. Also, the consequences of volunteering are still rarely discussed in a particular health care system context. Further studies need to analyze the measurement of volunteering development based on the nursing theory framework and explore the consequences of volunteering in the health care system related to the nursing care context.